Modification of multi-profile surfaces by compression plasma flows action of quasistationary high-current plasma accelerator - Ananin, S.I.; Astashynski, V.M.; Astashynski, V.V.; Chivel, Yu.A.; Kostyukevich, E.A.; Min'ko, L.Ya. (Вопросы атомной науки и техники, 2000)
The results of investigations into the action of compression plasma flows generated by the gas-discharge twostage quasistationary high-current plasma accelerator (QHPA) on multi-profile details are presented. Efficiency of the QHPA application to hardening treatment of samples from low- and medium-carbon steels with sufficient for practical purposes depth and microhardness of modified surface layer is shown.